Involvement of Village Women in overcoming poverty in t'eba Village - Adrianus Aluman (Institute of Computer Science (IOCS), 2023)
This study answers the above concerns by arguing that women's economic participation helps rural households lessen poverty. This study used ethnographic approaches to discover phenomena based on what poor households know, believe, feel, and do. Thus, the researcher took methodical notes. T'eba Village residents lived in poverty because they followed their predecessors' social and family practices. development of village women (housewives) to use local resources to meet market needs. urged the government to use culture to reduce household poverty. The cultural approach is to teach husbands and wives that ladies should help increase family income, not just manage what the husband produces. Women's economic boldness, especially in using local resources, defies patriarchal norms. Support village women's spirit without changing them. Government, community leaders, husbands, local institutions, NGOs, and academics mentor.